Analysis of Dynamic Behavior of Gas Bubbles and Solid Particles in an Oscillatory Baffled Reactor and Its Application to Design of Hydrogenation Proces - Mimo Nabeshima; Hideyuki Matsumoto; Anthony Basuni Hamzah; Shiro Yoshikawa; Shinichi Ookawara (Chemical Engineering Transactions, 2022)
In this paper, the dynamic behavior of gas bubbles and flow in a liquid-gas-solid oscillatory baffled reactor (OBR) was analyzed. A method based on baffle and oscillating flow induced vorticity was employed to analyze the dynamic gas bubble behavior and elucidate key parameters that govern the flow phenomena and reactor performances. Through visualization experiment for gas flow, it was observed that the fraction of gas bubbles inside OBR with oscillation increased up to 2.9 times than that without oscillation at the gas flow rate of 50 mL/min. Then it was observed that increasing the oscillation amplitude promoted the breakage of gas bubbles under the same conditions of oscillatory Reynolds number (Reo). On the other hand, particle image velocimetry (PIV) analysis revealed that the spatial distribution of streamlines and the magnitude of vorticity was almost same among operating conditions with different amplitudes of oscillation at the same Reo. In experiments for three-phase hydrogenation of 3-butyn-2-ol, the evaluated OBR showed higher reaction performance than the conventional packed bed reactor (PBR), and at the same Reo, the OBR with lower amplitude attained higher selectivity. It was considered that control of dynamic behavior of gas bubbles by the frequency and the amplitude of oscillation could enhance the reactor performances in the OBR.